2018
DOI: 10.3390/su10041202
|View full text |Cite|
|
Sign up to set email alerts
|

Dynamic Analysis of Ecological Environment Quality Combined with Water Conservation Changes in National Key Ecological Function Areas in China

Abstract: Abstract:The shortage of water resources is a key factor limiting the sustainability of the economy and society. Most of the 25 National Key Ecological Function Areas (NKEFAs) in China serve as a source and supplementation for numerous rivers and playing an important role in water resource conservation. Based on the analysis of eco-environmental quality changes in NKEFAs, this study analyzed the spatial pattern of water conservation services in 2000 and 2010 by using a water balance equation. The results indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…Var(S) = n(n − 1)(2n + 5) 18 (13) where x j and x i represent the EQ value of each pixel in year j and year i, and n is the length of the time series, which is 20 in this research. S is an intermediate variable.…”
Section: Theil-sen Median Trend Analysis and Mann-kendall Testmentioning
confidence: 99%
See 1 more Smart Citation
“…Var(S) = n(n − 1)(2n + 5) 18 (13) where x j and x i represent the EQ value of each pixel in year j and year i, and n is the length of the time series, which is 20 in this research. S is an intermediate variable.…”
Section: Theil-sen Median Trend Analysis and Mann-kendall Testmentioning
confidence: 99%
“…Previous research has established excellent methods to evaluate ecological quality. These include single indexes such as the normalized difference vegetation index (NDVI) [12] and fractional vegetation coverage (FVC) [13] that are usually used to assess the condition of vegetation, and synthetic models like the eco-environmental quality (EEQ) [14] and the Ecological Index (EI) [15], which have shown great potential in assessing ecological environmental quality precisely and comprehensively. However, there are still some limitations.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the eco-environment of Beijing is being threatened by various disturbances, and land resources play a key role in environmental ecosystem provision and eco-environment protection. However, with economic development and rapid urbanization, Beijing is experiencing increased resource pressures [25], [47].…”
Section: A Study Areamentioning
confidence: 99%
“…NKEFAs bear important ecological functions such as water conservation, soil conservation, windbreak sand fixation and biodiversity maintenance. Currently, China established the first batch of NKEFAs covering 436 counties at the end of 2010 (Xu et al, 2018), to which 240 new counties were added in 2016 (Figure 1). Since 2011, NKEFAs have become the largest regional ecological policy in China (Zhu and Chen, 2020).…”
Section: Introductionmentioning
confidence: 99%